Assisted Therapy with Vacuum and Floating Stoma: A New Way to Treat a Periostomal Abscess - Pérez, Andriun Duarte; Valle, Daniela Mendez; Medina, Laura Camila García; Burgos, Rosa Angélica Osorio; Reyes, José Daniel Sierra; Solano, Oscar Ivan Avendaño; Anguila, Jorge Julian Mendoza; Rojas, María Fernanda Riaño (Jour Med Resh and Health Sci, 2021)
An ostomy or stoma is the opening created surgically between a hollow viscus and the skin of the anterior abdominal wall, somewhat different from the floating stoma which is defined as a stoma characterized by the absence of fixation of this to the skin of the abdominal wall. These therapies have multiple variants that generate positive impacts and some situations in which negative effects can be observed in patients with complications of periosteal abscesses. The formation of a periostomal abscess is a rare condition, it generally occurs in 10% to 25% of cases of complications and is related to parietal inoculation or contamination of a peristomal hematoma. It has been described that the “floating stoma” therapy plus the vacuum therapy present in ostomized patients has had positive results as a therapy to treat patients who, in addition to being ostomized, have complications such as peristomal abscess, in fact, after the revision Bibliographic studies ensure that these can completely resolve periostomal abscesses, control, drain, correct and even allow faster closure of the abdominal wall, which is why it has been used as an effective therapy.